EFEKTIVITAS STRATEGI PEMBELAJARAN GALLERY WALK TERHADAP MINAT BELAJAR FIQH PADA SISWA KELAS VIII MTS SWASTA FAJRUL IMAN PATUMBAK - Ilhamdi Sinaga (Fakultas Agama Islam, 2021)
This study aims to determine the students' interest in learning Fiqh before and after being taught using the Gallery Walk learning strategy, and the effectiveness of the Gallery Walk learning strategy on the interest in learning Fiqh of the VIII grade students of MTs Swasta Fajrul Iman Patumbak. The population in this study were all students of class VIII MTs Swasta Fajrul Iman Patumbak for the academic year 2021/2022, totaling 152 students. The sample of this research was determined using random sampling technique as many as 38 students of class VIII. This research method is a descriptive method of correlational statistical techniques with a quantitative approach. Data collection methods used are: by conducting observations and questionnaires. The conclusions obtained from this study are: Interest in learning Fiqh of class VIII MTs Swasta Fajrul Iman Patumbak before the Gallery Walk learning strategy was applied got an average score of 66.11 including category C (medium). Interest in learning Fiqh students of class VIII MTs Private Fajrul Iman Patumbak before the Gallery Walk learning strategy was applied got an average score of 85.57 including category A (very good). The Gallery Walk learning strategy is effectively used in increasing students' interest in learning Fiqh with the provisions of tcount ttable, namely 9.89 1.688. With this provision, the hypothesis is accepted. With a significant level of = 0.05, the implementation of the Gallery Walk learning strategy helped 49.07% in increasing students' interest in learning Fiqh.